La evolución de la legislación farmacéutica en el Perú, y su implicancia en la obtención de los registros sanitarios de especialidades farmacéuticas en el laboratorio farmacéutico Instituto Quimioterápico S.A. - Iqfarma - Linares Ruiz, Diego Armando (2015)
The Law on Pharmaceutical Products, Medical Devices and Health Products No. 29459, published in November 2009, directs the regulation of these products replaces Chapter III of the General Health Law No. 26842. Through this Act has changed the most disputed aspects in Law No. 26842, establishing requirements for requesting the sanitary registration of pharmaceutical products that are necessary to ensure its effectiveness, safety and quality, also including the time needed for evaluation and that the cost of the health registration fee is depending on what that implies granting such registration, which also includes control activities and surveillance. It also restores the requirement of the sanitary authorization of operation prior to the start of operations after inspection to verify compliance with existing legal provisions. The Act also incorporates three specific chapters on access, rational use of pharmaceuticals, medical devices and health products as well as a chapter on research